2021
DOI: 10.17294/2330-0698.1791
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Echocardiographic Findings in Critically Ill COVID-19 Patients With or Without Prior Cardiac Disease

Abstract: Journal of Patient-Centered Research and Reviews (JPCRR) is an open access, peer-reviewed medical journal focused on disseminating scholarly works devoted to improving patient-centered care practices, health outcomes, and the patient experience. PurposeCoronavirus disease 2019 (COVID-19) presents with a spectrum of disease severity, the most serious cases requiring intensive care. Echocardiography is a front-line tool in evaluating cardiovascular complications of COVID-19 in the intensive care unit (ICU); we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…29 studies reported data about the prevalence of RVD 14 42 , while 7 reported about all-cause mortality according to RVD status 17 , 19 , 20 , 30 , 33 , 35 , 36 . 11 studies were held in Europe 16 , 18 21 , 33 36 , 38 , 40 , 8 in North America 23 , 25 , 26 , 28 , 29 , 37 , 41 , 42 , 3 in Asia 30 32 , and 7 in other geographical locations 14 , 15 , 17 , 22 , 24 , 27 , 39 , including 2 multinational studies 24 , 27 . Cohorts included were quite homogeneous in terms of mean age of the included patients (ranging from 52 years old to 68 years old); among sex, males were generally more represented than females (up to 84%).…”
Section: Resultsmentioning
confidence: 99%
“…29 studies reported data about the prevalence of RVD 14 42 , while 7 reported about all-cause mortality according to RVD status 17 , 19 , 20 , 30 , 33 , 35 , 36 . 11 studies were held in Europe 16 , 18 21 , 33 36 , 38 , 40 , 8 in North America 23 , 25 , 26 , 28 , 29 , 37 , 41 , 42 , 3 in Asia 30 32 , and 7 in other geographical locations 14 , 15 , 17 , 22 , 24 , 27 , 39 , including 2 multinational studies 24 , 27 . Cohorts included were quite homogeneous in terms of mean age of the included patients (ranging from 52 years old to 68 years old); among sex, males were generally more represented than females (up to 84%).…”
Section: Resultsmentioning
confidence: 99%
“…RVFAC was not significantly different between patients with severe and non-severe COVID-19, 44,46 nor survivors, and non-survivors. 47,55,56 However, RVFAC was found to be lower in COVID-19 patients with myocardial injury when compared with COVID-19 patients without myocardial injury. 57,58 Also, RVFAC does not seem to be significantly decreased even in COVID-19 patients with acute cor-pulmonale as compared with those with no acute cor-pulmonale.…”
Section: 4mentioning
confidence: 89%
“…70 However, in other studies among COVID-19 patients RVFAC was not significantly different between survivors compared with non-survivors. 47,55,56 Finally, a study by D'Alto et al demonstrated that right ventriculararterial uncoupling expressed as TAPSE/PASP is an independent predictor of mortality in COVID-19 patients. 29 With regards to LV parameters, mortality was found to be increased in patients who had reduced LV longitudinal strain (LS), left ventricular stroke volume index (LVSVi), cardiac index and tissue Doppler S' (systolic wave) velocity.…”
Section: Echocardiographic Predictors Of Mortality In Covid-19mentioning
confidence: 97%
“…Prior cardiac disease, right ventricular enlargement, and pulmonary hypertension were all associated with morbidity and mortality in these COVID-19 patients. [ 74 ]…”
Section: Common Covid-19 Risk Factorsmentioning
confidence: 99%